Food Provision at the Olympic Games in the New Millennium: A Meta-narrative Review - Fiona E. Pelly; Judith Tweedie; Helen O'Connor (SpringerOpen, 2023)
Abstract Background and objective The objective of this meta-narrative review was to identify, organise and map the literature on food provision and nutrition support at the summer and winter Olympic and Paralympic Games (OPG)  and similar major competition events over the past 21 years. This builds on a comprehensive update of a previous historical review of the evolution of food provision at the summer Olympic Games up until 2000 and considers contemporary issues such as the global pandemic and sustainability goals. Methods A range of sources included primary research and review articles, edited book chapters, theses, conference papers or abstracts, International Olympic Committee reports, Organising Committees' food vision and post-Games reports, independent professional reports, and media and periodicals including magazines and trade journals. The search strategy included four steps: a database search that complied with Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews criteria, a search of the Olympic Studies Centre, a review of reference lists for unpublished sources, and a Google search for additional media reports. The researchers followed an iterative process where emerging narratives were discussed, recorded and refined as data were extracted. Results The data from 229 records were extracted into a spreadsheet and grouped according to the type of evidence and specific event, then presented chronologically to give a perspective on the development of food provision and nutrition support. Eleven narratives emerged from the data extraction: 'description of meals, menus and food', 'vision of the food provision', 'food safety', 'catering company involvement', 'sponsorship or contracts with food companies', 'athlete perspective', 'stakeholder perspective', 'athlete food intake,' 'nutrition input in food provision', 'food environment' and 'sustainability'. Conclusion Results suggest that athletes' dining expectations, organising committee budgets, expert input and current global trends have led to food delivery changes. The OPG food environment has the capacity to positively influence the dietary choices of athletes and teams, while evolving to meet contemporary global challenges such as COVID-19 and sustainability targets.